Komposisi Vegetasi Lantai Di Kawasan Hutan Produksi Terbatas Fatunisuan Kabupaten Timor Tengah Utara - Orince Luruk Teti; Yoseph Nahak Seran; Florian Mayesti Prima Remba Makin (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The purpose of this study was to analyze the composition of floor vegetation in the Fatunisuan Limited Production Forest Area (HPT), North Central Timor Regency. The study was conducted in July – September 2022. The method used is the plot method of 20 plots with sizes of 5 m x 5 m (bush), 2 m x 2 m (herbs), and 1 m x 1 m (shrubs). The results showed that the composition of the vegetation obtained was 22 species consisting of 7 species of shrubs, 9 species of herbs, and 6 species of shrubs. The Important Value Index (INP) was dominated by the shrub level of Chromolaena odorata L. (53.39%.), the herb Hedysarm triquetrum (50.52%), and shrub Mimosa pudica L. (61.72%). Environmental factors also play a role in the presence of floor vegetation such as soil pH with an average of 6.45, soil moisture with an average of 34.97%, air humidity with an average of 61.66%, and air temperature of 41.01ºC. The benefits of this study are to increase the knowledge of researchers about the composition, diversity and potential of floor plants, and obtain information about the diversity of plant species in the floor vegetation group.